Synoptic-scale transport drives wintertime secondary organic aerosol variability and high-PM episodes in Seoul - Suk Hyun Lee; Taekyu Joo; Suyeon Choi; Hye-Ji Lee; Seung-Bok Lee; Kwang Rae Kim; Hakmyeong Lim; Meehye Lee; Kyung Hwan Kim (Environmental Research, 2026)

Quantitative analysis of PM2.5 oxidative potential: Insights into the role of organic compounds and sources - Ji-Hyeon Koo; Sung-Won Park; Hyo-Won Lee; Pyung-Rae Kim; Ji-Won Jeon; Kyung-Hwan Kwak; Seung-Muk Yi; Jeffrey L. Collett; Young-Ji Han (Journal of Hazardous Materials, 2025)

Physics-based landslide susceptibility machine learning model for mountainous solar power plants - Enok Cheon; Jeong-Yeon Yu; Hwan-Hui Lim; Seung-Rae Lee; Tae-Hyuk Kwon; Ki-Il Song (Natural Hazards, 2025)
Between 2018 and 2020, several landslides occurred on solar power plants constructed on hillsides after extreme rainfall in South Korea. This study presents a physics-informed machine-learning model to conduct real-time physically-based landslide susceptibility assessment on solar panels installed on mountains. Through a statistical filtering process, fourteen landslide triggering factors related to the topography, soil geotechnical properties, soil hydrological properties, meteorological effects, and solar panels model were selected. While accounting for the presence of solar panels, 136,262 numerical simulations of rainfall infiltration transient seepage and slope stability analyses were performed. Among three machine learning models (random forest, support vector regression, and multi-layer perceptron) developed from numerical simulation data points, the multi-layer perceptron (MLP) model showed the highest prediction accuracy (R $$^{2}$$ 2 = 96% and mean square error = 0.001) without indicating overfitting. The sensitivity analysis on the developed MLP model indicated that the soil strength properties strongly influenced the factors of safety (FOS), but hydraulic properties showed a relatively small impact. The developed MLP model was applied to a solar power plant in Jangsu-gun, Jeonbuk-do, South Korea, to verify the model’s predictability and showed the applicability of the developed MLP model for physically-based landslide susceptibility assessment. Furthermore, the Jangsu-gun example demonstrated the potentiality of the MLP model for a landslide early warning system (LEWS) for mountainous solar power plants thanks to its fast computational speed at predicting real-time FOS.

Estimation of Potentially Toxic Substances and Health Risks in VOCs in Urban Areas of Seoul - Shin-Young Park; Hyeok Jang; Kwang-rae Kim; Hyun-ju Ha; Yuri Choi; Seung-mi Kwon; Yongsuk Choi; Ju-Sung Park; Cheol-Min Lee (Water, Air, & Soil Pollution, 2025)

Estimation of soil particle fractions in Korea based on spectral imaging and ANN for UAV-based field applications - Hwan-Hui Lim; Enok Cheon; Woojae Jang; Tae-Hyuk Kwon; Jin-Woo Cho; Seung-Rae Lee (Remote Sensing Applications: Society and Environment, 2025)

Characteristics of elevated PM2.5 events driven by enhanced organic compound concentrations in a South Korean residential city - Hye-Ji Lee; Hyo-Won Lee; Sung-Won Park; Ji-Won Jeon; Pyung-Rae Kim; Kyung-Hwan Kwak; Young-Ji Han; Thomas M. Holsen; Seung-Ha Lee; Hyun-Gu Jung; Seung-Hwan Cha; Jung-Min Park; et al. (Atmospheric Environment, 2025)

Role of factors controlling diurnal variation of cold-season formaldehyde during Satellite Integrated Joint Monitoring of Air Quality 2021 campaign - Lim-Seok Chang; Soi Ahn; Min-Suk Bae; Seung-Myung Park; Junsu Gil; Kwang-Rae Kim; Gangwoong Lee; Taehyoung Lee; Jung-Hun Woo; Rokjin Park; Hyeong-Ahn Kwon; Gyo-Hwang Choo; et al. (Science of The Total Environment, 2025)

Machine learning and hyperspectral imaging to predict soil water content: methodology and field validation - Hwan-Hui Lim; Enok Cheon; Seung-Rae Lee (Earth Science Informatics, 2025)

Engineering robust interfaces for enhanced Li metal and ceramic electrolyte compatibility in solid-state systems - Rae-Hyun Lee; Ha-Na Jo; Chea-Yun Kang; Jong-Kyu Lee; Hyun-Soo Kim; Bong-Soo Jin; Kyong-Nam Kim; Jung-Rag Yoon; Seung-Hwan Lee (Chemical Engineering Journal, 2024)

Seismic performance of sheet pile walls in liquefiable soil using centrifuge tests and an assessment of nonlinear effective stress analysis using PM4Sand - Satish Manandhar; Seung-Rae Lee; Majid T. Manzari; Gye-Chun Cho (Soil Dynamics and Earthquake Engineering, 2024)

Determination of average growth rate based on statistical relationships using geomorphological and geotechnical variables in predictive debris flow simulations - Joon-Young Park; Seok Yoon; Deuk-Hwan Lee; Seung-Rae Lee; Hwan-Hui Lim (Geomorphology, 2024)

Facile and rapid fabrication of wearable biosensors via femtosecond laser-directed micro-patterning with large-sized reduced graphene oxide for physiological monitoring - Hae-In Moon; Sungil Kim; Jeong Eun Byun; Young Won Kim; Yeon Wook Jung; Seung Geun Jo; Yujin Shin; Yeoul Kang; Sang Jun Kim; Eun-Su Lee; Hyung-Jong Lee; Min-Cheol Oh; et al. (Chemical Engineering Journal, 2024)

Eye development and developmental expression of crystallin genes in the long arm octopus, Octopus minor - Kyoung-Bin Ryu; Gun-Hee Jo; Young-Chun Gil; Donggu Jeon; Na-Rae Choi; Seung-Hyun Jung; Seonmi Jo; Hye Suck An; Hae-Youn Lee; Seong-il Eyun; Sung-Jin Cho (Frontiers in Marine Science, 2023)
The eye of a cephalopod is a well-known example of convergent evolution and resembles the vertebrate eye. Although cephalopods and vertebrates exhibit similar eye form and function, they differ in visual origin and structure. The common long-arm octopus ( Octopus minor ) is a good model system in evolutionary and developmental studies due to its highly centralized nervous system, shorter life cycle, and specific camera-type eyes that contribute to convergence with vertebrate eye. Lens-containing eyes represent a significant improvement of simple eye and have evolved by convergent mechanisms, a variety of lenses and corneas containing diverse crystallin. The diversity and taxon-specificity of lens crystallin is indicative of convergent evolution of crystallin roles. Previous studies have focused on morphological, ontogenetic and phylogenetic analysis of crystallin to understand the evolution of lens-containing eyes. However, little is known about the functional analysis of taxon-specific crystallin genes at the molecular level in the eye of O. minor . Using an embryonic staging system of Octopus minor as a model system, we investigated fifteen genomes and the structure of eye by immunohistochemistry, phalloidin staining and the three-dimensional structures. We also obtained the crystallin-related genes ( i . e ., α-, S-, and Ω-crystallin) from the transcriptome data of O. minor . Subsequent molecular phylogenetic analysis based on these genes revealed a distinct divergence pattern among the three gene classes and further suggested the evidence supporting the taxon-specific convergent evolutionary trend. We analyzed the expression pattern of crystallin genes via in situ hybridization during developmental stages. All crystallin genes are commonly expressed in the lentigenic cells of ciliary body. The α-crystallin found in cephalopods was also expressed at the peripheral region of the lens including ciliary body, suggesting a possible role in lens formation in cephalopods. This study will provide information on the eye development of O. minor and support the typical models of convergent evolution by demonstrating independent recruitment of different types of proteins to fulfill their unique visual role.

First report of plantago asiatica mosaic virus infecting scarlet geranium (Pelargonium inquinans) worldwide - Hyo-Jeong Lee; Seung-Hyeon Bak; Hyeong Woo Lee; Jin-Sung Hong; Rae-Dong Jeong (Journal of Plant Pathology, 2022)

Assessment of barrier location effect on debris flow based on smoothed particle hydrodynamics (SPH) simulation on 3D terrains - Shin-Kyu Choi; Joon-Young Park; Deuk-Hwan Lee; Seung-Rae Lee; Yun-Tae Kim; Tae-Hyuk Kwon (Landslides, 2021)
Debris flows are one of the perilous landslide-related hazards due to their fast flow velocity, large impact force, and long runout, in association with poor predictability. Debris-flow barriers that can minimize the energy of debris flows have been widely constructed to mitigate potential damages. However, the interactions between debris flows and barriers remain poorly understood, which hampers the optimal barrier installation against debris flows. Therefore, this study examined the effect of barrier locations, in particular source-to-barrier distance, on velocity and volume of debris flows via the numerical approach based on smoothed particle hydrodynamics (SPH). A debris-flow event was simulated on a 3D terrain, in which a closed-type barrier was numerically created at predetermined locations along a debris-flow channel, varying the source-to-barrier distance from the initiation point. In all cases, the closed-type barrier significantly reduced the velocity and volume of the debris flows, compared to the cases without a barrier. When the initial volume of source debris was small, or when the flow path was short, the barriers effectively blocked the debris flow regardless of the source-to-barrier distance. However, with a long flow path, installation of the barrier closer to the initiation location appeared more effective by preventing the debris volume from growing by entrainment. Our results contribute to a better understanding of how source-to-barrier distance influences debris-flow behavior, and show that the methodology presented herein can be further used to determine optimum and efficient designs for debris-flow barriers.

A shallow slide prediction model combining rainfall threshold warnings and shallow slide susceptibility in Busan, Korea - Ananta Man Singh Pradhan; Seung-Rae Lee; Yun-Tae Kim (Landslides, 2019)

A method to develop the input parameter database for site-specific debris flow hazard prediction under extreme rainfall - Nikhil Nedumpallile Vasu; Seung-Rae Lee; Deuk-Hwan Lee; Joonyoung Park; Byung-Gon Chae (Landslides, 2018)

Effects of backcrossing on quality of strawberry fruit - Sun Yi Lee; Seung Yu Kim; Dae Young Kim; Ho Jeong Jeong; In Seok Um; Il Rae Rho (Horticulture, Environment, and Biotechnology, 2018)

Combined Poly(Lactide-Co-Glycolide) Microspheres Containing Diphtheria Toxoid for a Single-shot Immunization - Hye Seung Woo; Sung Rae Kim; Mikyeong Yoon; Eun Seok Lee; In Ho Chang; Young Mi Whang; Do Ik Lee; Myung Joo Kang; Young Wook Choi (AAPS PharmSciTech, 2018)

Intraspecific variation of gene structure in the mitochondrial large subunit ribosomal RNA and cytochrome c oxidase subunit 1 of Pyropia yezoensis (Bangiales, Rhodophyta) - Il Ki Hwang; Seung-Oh Kim; Mi Sook Hwang; Eun-Jeong Park; Dong-Soo Ha; Sang-Rae Lee (Algae, 2018)

Effect of gypsum on exchangeable sodium percentage and electrical conductivity in the Daeho reclaimed tidal land soil in Korea—a field scale study - Hyuck Soo Kim; Kwon-Rae Kim; Seung-Heon Lee; Anitha Kunhikrishnan; Won-Il Kim; Kye-Hoon Kim (Journal of Soils and Sediments, 2018)

Effect of house dust mite on neutrophil apoptosis by cytokine secretion in lymphocytes - Na Rae Lee; Ji-Sook Lee; Seung Yeop Baek; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Soo Jin Lee; In Sik Kim (Molecular & Cellular Toxicology, 2016)

House dust mite allergen suppresses neutrophil apoptosis by cytokine release via PAR2 in normal and allergic lymphocytes - Na Rae Lee; Seung Yeop Baek; Ayoung Gu; Da Hye Kim; Seong Yeol Kim; Ji-Sook Lee; In Sik Kim (Immunologic Research, 2016)

Different anti-apoptotic effects of house dust mite allergen on eosinophil apoptosis between atopic and non-atopic asthmatic subjects - In Sik Kim; Mi Ae Im; Na Rae Lee; Seung Yeop Baek; Beom Seok Park; Ayoung Gu; Da Hye Kim; Ji-Sook Lee (Molecular & Cellular Toxicology, 2015)

Protective effect of a novel herbmedicine, Hepad, on apoptosis of SH-SY5Y cells and a rat model of Parkinson’s disease - Seung Yeop Baek; Na Rae Lee; Da Hye Kim; Ayoung Gu; Seong Yeol Kim; Dae-Yong Song; Dong-Hee Kim; Hak Joo Choi; Byung-Jun Park; In Sik Kim (Molecular & Cellular Toxicology, 2015)

Complete mitochondrial genome sequence of Pyropia yezoensis (Bangiales, Rhodophyta) from Korea - Mi Sook Hwang; Seung-Oh Kim; Dong-Soo Ha; Jee Eun Lee; Sang-Rae Lee (Plant Biotechnology Reports, 2014)

Cover Placement on Dredged Marine Clay Reclaimed Deposit - Hyunku Park; Seung-Rae Lee; Sung-Hyun Jee (Marine Georesources & Geotechnology, 2014)

Complete sequence and genetic features of the mitochondrial genome of Pyropia tenera (Rhodophyta) - Mi Sook Hwang; Seung-Oh Kim; Dong-Soo Ha; Jee Eun Lee; Sang-Rae Lee (Plant Biotechnology Reports, 2013)

The effect of ozone and aerosols on the surface erythemal UV radiation estimated from OMI measurements - Joonsuk Lee; Won Jun Choi; Deok Rae Kim; Seung-Yeon Kim; Chang-Keun Song; Jun Suk Hong; Youdeog Hong; Sukjo Lee (Asia-Pacific Journal of Atmospheric Sciences, 2013)

Cadmium resistance in tobacco plants expressing the MuSI gene - Young-Nam Kim; Ji-Seoung Kim; Sang-Gyu Seo; Youngwoo Lee; Seung-Woo Baek; Il-Sup Kim; Ho-Sung Yoon; Kwon-Rae Kim; Sun-Hyung Kim; Kye-Hoon Kim (Plant Biotechnology Reports, 2011)

Alteration of floral organ identity by over-expression of IbMADS3-1 in tobacco - Mi-Rae Shin; Sang-Gyu Seo; Ji-Seoung Kim; Seo-Bum Joen; Seung-Won Kang; Gung-Pyo Lee; Suk-Yoon Kwon; Sun-Hyung Kim (Transgenic Research, 2011)

Monitoring of selected veterinary antibiotics in environmental compartments near a composting facility in Gangwon Province, Korea - Yong Sik Ok; Sung-Chul Kim; Kwon-Rae Kim; Sang Soo Lee; Deok Hyun Moon; Kyoung Jae Lim; Jwa-Kyung Sung; Seung-Oh Hur; Jae E. Yang (Environmental Monitoring and Assessment, 2011)

A volumetric study of the corpus callosum in 20s and 40s Korean people - Beob-Yi Lee; Jin-Hun Sohn; Mi-Hyun Choi; Su-Jeong Lee; Hyo-Seong Kim; Jae-Woong Yang; Jin-Seung Choi; Hyung-Sik Kim; Jeong-Han Yi; Gye-Rae Tack; Soon-Cheol Chung (Brain Structure and Function, 2009)

Comparison Between Shear Behaviors of Overconsolidated Nakdong River Sandy Silt and Silty Sand - Khin Swe Tint; Seung Rae Lee; Young Su Kim (Marine Georesources & Geotechnology, 2009)

Touch-induced gene (IbTCH1) from sweet potato [Ipomoea batatas (L.) Lam.]: molecular cloning and functional analysis - Sang-Gyu Seo; Ji-Seong Kim; Seung-Won Kang; Mi-Rae Shin; You-Sun Yang; Gung-Pyo Lee; Jin-Sung Hong; Sun-Hyung Kim (Plant Biotechnology Reports, 2008)

Observations of Forsythia koreana methanol extract on mast cell-mediated allergic reactions in experimental models - In-Young Choi; Phil-Dong Moon; Hyun-Na Koo; Noh-Yil Myung; Su-Jin Kim; Ji-Hyun Lee; Se-Hee Han; Goo Moon; Sung-Yum Seo; Hyun-Jea Sung; Rae-Kil Park; Hyun-Ja Jeong; et al. (In Vitro Cellular & Developmental Biology - Animal, 2007)

Temperature Effect on Migration of Zn and Cd Through Natural Clay - Nam Young Do; Seung Rae Lee (Environmental Monitoring and Assessment, 2006)

Effect of Temperature on Single and Competitive Adsorptions of Cu(II) and Zn(II) onto Natural Clays - Nam Young Dho; Seung Rae Lee (Environmental Monitoring and Assessment, 2003)

Prediction of Leachate Level in Kimpo Metropolitan Landfill Site by Total Water Balance - Nam Yung Dho; Ja Kong Koo; Seung Rae Lee (Environmental Monitoring and Assessment, 2002)